Mequindox Induced Genotoxicity and Carcinogenicity in Mice - Liu, Qianying; Lei, Zhixin; Wu, Qin; Huang, Deyu; Xie, Shuyu; Wang, Xu; Pan, Yuanhu; Yuan, Zonghui (Frontiers in Pharmacology, 2018)
Mequindox (MEQ), acting as an inhibitor of deoxyribonucleic acid (DNA) synthesis, is a synthetic heterocyclic N-oxides. To investigate the potential carcinogenicity of MEQ, four groups of Kun-Ming (KM) mice (50 mice/sex/group) were fed with diets containing MEQ (0, 25, 55 and 110 mg/kg) for one and a half years. The result showed adverse effects on body weights, feed consumption, hematology, serum chemistry, organ weights, relative organ weights, and incidence of tumors during most of the study period. Treatment-related changes in hematology, serum chemistry, relative weights and histopathological examinations revealed that the hematological system, liver, kidneys and adrenal glands, as well as the developmental and reproductive system, were the main targets after MEQ administration. Additionally, MEQ significantly increased the frequency of micronucleated normochromatic erythrocytes in bone marrow cells of mice. Furthermore, MEQ increased the incidence of tumors, including mammary fibroadenoma, breast cancer, corticosuprarenaloma, haemangiomas, hepatocarcinoma and pulmonary adenoma. Interestingly, the higher incidence of tumors was noted in M25 mg/kg group, the lowest dietary concentration tested, which was equivalent to approximately 2.25 and 1.72 mg/kg b.w./day in females and males, respectively. It was assumed that the lower toxicity might be a reason for its higher tumor incidence in M25 mg/kg group. This finding suggests a potential relationships among the dose, general toxicity and carcinogenicity in vivo, and further study is required to reveal this relationship. In conclusion, the present study demonstrates that MEQ is a genotoxic carcinogen in KM mice.